2017
DOI: 10.15226/2476-2431/2/1/00115
|View full text |Cite
|
Sign up to set email alerts
|

Adverse Drug Reactions among Patients Admitted to Eritrean Hospitals: Prevalence Causes and Risk Factors a prospective analysis of 5848 patients

Abstract: Background: Eritrea is one of the developing countries which has shortage of physicians at all levels. As a result, lower health cadres are authorized to prescribe medicines. In addition, due to shortages of laboratory setups, lab-based therapeutic monitoring is a challenge. The Eritrean society is also highly involved in self-medication; all these could have contributions to ADRs. Thus, the objective of the study is to investigate and analyze the prevalence, causes, and risk factors of Adverse Drug Reactions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
42
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(44 citation statements)
references
References 24 publications
1
42
1
Order By: Relevance
“…Regarding associations with age, the association between ADR occurrence and prematurity which is attributable to reduced drug metabolism and clearance is also well established [26]. Previous hospital-based surveys in the United Kingdom [18,27], United States [17], and in sub-Saharan Africa [20] have also, similar to our finding, described an association between ADR occurrence and later childhood. This association has been explained by older children's ability to communicate their ADRs better than younger children [27].…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Regarding associations with age, the association between ADR occurrence and prematurity which is attributable to reduced drug metabolism and clearance is also well established [26]. Previous hospital-based surveys in the United Kingdom [18,27], United States [17], and in sub-Saharan Africa [20] have also, similar to our finding, described an association between ADR occurrence and later childhood. This association has been explained by older children's ability to communicate their ADRs better than younger children [27].…”
Section: Discussionsupporting
confidence: 88%
“…High mortality and an association with medication error was also seen in the Ethiopian adverse drug event survey [22], where 9% of adverse drug events resulted in permanent harm or death, with three of the four events that resulted in permanent harm in that survey being due to medication error. Higher mortality rates than ours occurred in Eritrea, where 19/114 (17%) children admitted for ADRs died due to their ADRs [20], and in Nigeria, where 2/12 (17%) of children admitted for ADRs died due to their ADRs [21]. While our fatality rate may seem reassuringly low against these sub-Saharan African studies, it should be noted that an additional seven ADRs in our survey were considered nearfatal, meaning that 20% of serious ADRs may potentially have resulted in children's deaths.…”
Section: Discussioncontrasting
confidence: 58%
See 1 more Smart Citation
“…Anemia which was mostly associated with Zidovudine was the third most serious ADR, unlike previous studies that found anemia to be the most serious ADR [12, 16, 21]. This difference could be either due to the inappropriate laboratory monitoring of the patients on HAART in Halibet hospital which undermines the real frequency or due to the nature of this study.…”
Section: Discussionmentioning
confidence: 59%
“…Limited study has been conducted on the adverse effect of ART in Sub-Saharan countries, such as Eritrea, despite having high prevalence of HIV. A five-month prospective study conducted in Eritrea by Russom et al 2017 [12] aimed at measuring ADR related hospital admissions in all Eritrean hospitals showed first line ART drugs (Zidovudine/lamivudine and Tenofovir/lamivudine) to be among the top three drugs implicated in causing ADR related deaths. The study further added that ART associated anemia accounted for 20.8% of the ADR related deaths which could have easily been prevented by appropriate laboratory monitoring.…”
Section: Introductionmentioning
confidence: 99%